(untitled) (Journal of Indonesian Legal Studies, 2024)
The enactment of Law No. 15 of 2019, which established the Post-Legislative Scrutiny (PLS) institution, marked a pivotal shift in the formation of laws and regulations (PUU) in Indonesia. This legislation ushered in a comprehensive cycle for PPU, fundamentally altering the landscape of legislative processes. Despite this progress, a prevailing assumption persists that the PLS mechanism is solely within the purview of the People’s Representative Council (DPR) concerning national laws, while oversight of Regional Regulations (Perda) falls under the authority of the Regional People’s Representative Council (DPRD), with limited discourse on the latter’s role in academic circles. This study endeavors to elucidate the theoretical underpinnings of PLS within international parliamentary frameworks, analyze the regulatory framework of PLS Perda as delineated in Law No. 23/2014 and PP No. 12/2018, scrutinize its implementation in Provincial DPRD Rules of Procedure, and advocate for bolstering the DPRD’s role in conducting PLS Perda. Findings reveal a lexicon of PLS terminology within Indonesian legislative context, alongside a bifurcation of PLS Perda oversight between the DPD and DPRD. Alarmingly, a staggering majority (93.10%) of Provincial DPRDs nationwide have yet to formalize PLS procedures in their Rules of Procedure, with only the DIY Provincial DPRD demonstrating comprehensive implementation among the 34 surveyed. The imperatives for empowering DPRD’s Bapemperda include evaluating Regional Regulations’ efficacy, fostering legal coherence, preempting discriminatory legislation, enhancing legislative quality through experiential learning, and resolving the institutional dualism between DPD and DPRD in PLS Perda oversight. These measures not only fortify legislative processes but also mitigate jurisdictional ambiguities, ensuring robust governance at both national and regional levels.